Pengembangan Museum Sonobudoyo Sebagai Daya Tarik Wisata Edukasi Di Era New Normal - Ditha, Risa Ayu; Prasetyo, Danang; Syamsu, Moch. Nur (JURNAL DESTINASI PARIWISATA, 2021)
Yogyakarta is known as the City of Students and the City of Tourism. This is due to the fact that there are many universities and also the best schools in Indonesia. Musuem is an institution or institution which is a place for storing, caring for, researching and utilizing material objects which are evidence of the results of human, natural and environmental culture with the aim of preserving culture and also for a form of protection. One of the museums which is a tourist destination that is very often visited by tourists who come to Yogyakarta is the Sonobudoyo Museum. This study aims to find out what efforts the manager made in developing the Sonobudoyo unit I museum as an educational tour in the new normal era, to know the efforts made by the government to increase visits to the Sonobudoyo museum in the new normal era, and to know the assessments and expectations of visitors regarding Sonobudoyo Museum Unit I as an object of educational tourism attraction in Yogyakarta in the new normal era. The research method used is qualitative. With 2 (two) types of data, namely primary data and secondary data which the authors get from the results of observations, interviews, questionnaires, and documentation. The data analysis used is a SWOT analysis. The results of this study indicate that the Sonobudoyo Museum can positively be used as an educational tour in the new normal era with regulatory changes and technological additions that make the Sonobudoyo Museum ready and alert in accepting tourist visits in the new normal era. Museums can be used as educational tours that can increase visitor interest in learning activities. Moreover, if the majority of visitors are students from elementary, middle school, college students can get useful knowledge when they come to the museum. Keyword: museum, tourism attraction, edutourism, new normal